2009
DOI: 10.1155/2009/693458
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Cachexia among Cancer Patients Based on Four Definitions

Abstract: Objectives. Estimate and compare the proportion of cancer patients with cachexia using different definitions from available clinical data. Methods. Electronic medical records were examined to estimate the proportion of cancer patients with cachexia using 4 definitions: (1) ICD-9 diagnostic code of 799.4 (cachexia), (2) ICD-9 diagnosis of cachexia, anorexia, abnormal weight loss, or feeding difficulties, (3) prescription for megestrol acetate, oxandrolone, somatropin, or dronabinol, and (4) ≥5% weight loss. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 15 publications
0
101
0
6
Order By: Relevance
“…Among the problems associated with the translation of DR into clinical applications is that chronic DR delays but does not stop the progression of the disease (Mukherjee et al, 2004;Bonorden et al, 2009;Shelton et al, 2010), and that this delay will occur for only a subset of malignancies (Kalaany and Sabatini, 2009). Although weight loss and cachexia in the early stages of cancer progression are not as common as thought (Tisdale, 2002;Fearon et al, 2003;Fox et al, 2009), the B15% loss of body mass index caused by a moderate (20%) calorie restriction (Racette et al, 2006) would prevent its use in the great majority of cancer treatment scenarios. In addition, the effect of long-term restriction in delaying wound healing and impairing immune function Kristan, 2008;Reed et al, 1996) may impose a significant risk to cancer patients receiving chemotherapy, surgery or immunity-based treatments (Kim and Demetri, 1996).…”
Section: Dr and Cancer Treatmentmentioning
confidence: 99%
“…Among the problems associated with the translation of DR into clinical applications is that chronic DR delays but does not stop the progression of the disease (Mukherjee et al, 2004;Bonorden et al, 2009;Shelton et al, 2010), and that this delay will occur for only a subset of malignancies (Kalaany and Sabatini, 2009). Although weight loss and cachexia in the early stages of cancer progression are not as common as thought (Tisdale, 2002;Fearon et al, 2003;Fox et al, 2009), the B15% loss of body mass index caused by a moderate (20%) calorie restriction (Racette et al, 2006) would prevent its use in the great majority of cancer treatment scenarios. In addition, the effect of long-term restriction in delaying wound healing and impairing immune function Kristan, 2008;Reed et al, 1996) may impose a significant risk to cancer patients receiving chemotherapy, surgery or immunity-based treatments (Kim and Demetri, 1996).…”
Section: Dr and Cancer Treatmentmentioning
confidence: 99%
“…The proximal cause of death in the sipuleucel-T trials was not reported. However, in general, approximately 60% to 70% of patients with advanced prostate cancer have cachexia (21)(22)(23). Several cytokines (e.g., TNFa, IL-1, IL-6, and IL-8) are elevated in patients with prostate cancer and may be involved in cachexia (21).…”
Section: Mechanism Of Therapeutic Efficacymentioning
confidence: 99%
“…Interestingly, the incidence of weight loss vary greatly according to the tumor site: the greatest weight loss was seen among patients with solid tumors (e.g. gastric, pancreatic, lung, colorectal, head and neck) (16). In particular, those patients with upper gastrointestinal and lung cancer are more predisposed to this condition with a prevalence of cachexia up to 80% and 60% respectively (17).…”
Section: Epidemiology Of Sarcopenia and Cancer Cachexiamentioning
confidence: 99%